Autoimmunity to a liver membrane lipoprotein and liver damage in alcoholic liver disease. Issue 2 (February 1981) - Perperas, A; Tsantoulas, D; Portmann, B; Eddleston, A L; Williams, R
Abstract : Antibodies reacting with a liver membrane lipoprotein (LSP) have been detected by radioimmunoassay in the sera of 15 (27%) of 55 patients with alcohol-related liver lesions. There was a close association between the presence of the anti-LSP antibody and the findings on liver biopsy of a lymphocytic infiltrate in the portal tracts together with piecemeal necrosis of periportal hepatocytes. These histological features are characteristically found in the autoimmune disorder of chronic active hepatitis, in which anti-LSP antibodies are almost invariably present. It is suggested that in these cases of alcoholic liver disease there is loss of tolerance, and continued production of anti-LSP could promote periportal inflammation and accelerate the progression to cirrhosis. In the cases of acute alcoholic hepatitis without periportal inflammation studied, anti-LSP was not detected demonstrating that production of this autoantibody is not simply secondary to liver damage.